Tangible Cultural Heritage Revitalization of Lasem as one of the Oldest China Towns in Java Island, Indonesia - Wahyu Tyas Pramono; Choirul Amin; Basyar Ihsan Arijuddin; Nirma Lila Anggani; Muhammad Iqbal Taufiqurrahman Sunariya (Mahesa Research Center (PT. Mahesa Global Publishing), 2026)
As a small town with the nickname Little Chinese or “Petit Chinois” in Java Island of Indonesia, Lasem has undergone a transformation due to political transitions, changes in economic patterns, and modernization which have changed its identity in general. Chinese settlements that have existed since the 14-15th centuries have become historical evidence of the existence of Chinese communities who migrated to Southeast Asia, which initiated the birth of the “Peranakan” culture. In 2021, the Ministry of Public Works and Housing of the Republic of Indonesia revitalized the Lasem cultural heritage site with the aim of protecting historical values and infrastructure both related to Chinese culture and Islamic culture in Lasem. This paper reviews the cultural elements of Chinese culture that were lost in Lasem, and which are still intact, as well as reviews the positive and negative sides of the government's revitalization project implemented in the Little Chinese of Karangturi block and Islamic cultural heritage in the city square area. The result was that several physical cultural heritages had lost their authenticity due to revitalization that was not in accordance with the 2021 detailed engineering design (DED). However, marketing through social media has increased tourism activities through branding Little Tiongkok heritage and several festival celebrations in Lasem have attracted thousands of visitors.